Pengaruh Putaran Benda Kerja Dan Tool Feeding Terhadap Kekasaran Permukaan Dengan Menggunakan Metode Pemakanan Orthogonal Pada Proses Turn-Milling - Evon Yulianto; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The turn-milling test has three methods in the process of working are orthogonal, tangential, and co-axial. In this methods turn-milling test produces a varied surface roughness. To optimize the surface roughness in this method orthogonal turn-milling then the variation of testing is done at the rotation velocity of workpiece and feeding velocity. The testing process of turn-milling machining is performed on conventional lathe with the addition of a rotary tool. The purpose of this research is to get the optimum rotation velocity of workpiece and feeding velocity of the value of surface roughness and To know the effect of velocity rotation of workpiece and feeding velocity to surface roughness value. With increasing velocity rotation of workpiece and feeding velocity, velocity rotation of the workpiece increased will affect the surface roughness value. Based on the roughness class N, the 630 rpm rotation of workpiece parameters with feed rate of 0.060 mm is a good parameter in this study because it produces a roughness value of 1.489 μm lower than the other test.Keywords : Turn-milling, Round, Feeding, Roughness.